MicroRNA-210-5p Contributes to Cognitive Impairment in Early Vascular Dementia Rat Model Through Targeting Snap25 - Ren, Zhenxing; Yu, Junlong; Wu, Zimei; Si, Wenwen; Li, Xianqian; Liu, Yuqing; Zhou, Jianhong; Deng, Rudong; Chen, Dongfeng (Frontiers in Molecular Neuroscience, 2018)
Vascular dementia (VD) is the most common form of dementia in elderly people. However, little is understood about the role of microRNAs (miRNAs) involved in cognitive impairment in early VD. Here, a VD model induced by chronic cerebral ischemia and fetal bovine serum (FBS)-free cell model that detects synapse formation was established to investigate the function of miRNAs in early VD. The microarray analysis and real-time reverse transcription polymerase chain reaction (RT-PCR) showed that miR-210-5p increased significantly in the hippocampus of rats with 4 weeks of ischemia. The VD model rats also displayed significant cognitive deficits and synaptic loss. The overexpression of miR-210-5p decreased the synaptic number in primary hippocampal neurons, whereas specific suppression of miR-210-5p resulted in the formation of more synapses. Additionally, intracerebroventricular (ICV) injection of miR-210-5p agomir to VD rats aggravated phenotypes of cognitive impairment and synaptic loss. These VD-induced phenotypes were effectively attenuated by miR-210-5p antagomir. Moreover, bioinformatic prediction revealed that synaptosomal-associated protein of 25 KDa (Snap25) mRNA is targeted by miR-210-5p. The miR-210-5p decreased the luciferase activities of 3’ untranslated region (3’UTR) of Snap25 mRNA. Mutation of predicted miR-210-5p binding sites in the 3’ UTR of Snap25 mRNA abolished the miR-210-5p-induced decrease in luciferase activity. Western blot and immunofluorescence staining confirmed that miR-210-5p targets Snap25. Finally, RT-quantitative PCR (qPCR) and immunofluorescence staining detected that miR-210-5p agomir downregulated Snap25 expression in the cornu ammonis1 (CA1) region of hippocampi in VD rats, whereas miR-210-5p antagomir upregulated Snap25 expression. Altogether, miR-210-5p contributes to cognitive impairment in chronic ischemia-induced VD model through the regulation of Snap25 expression, which potentially provides an opportunity to develop a new therapeutic strategy for VD.